New developments in neutrino physics - Alberico, W. M.; Bilenky, S. M. (HNPS Advances in Nuclear Physics, 2020)
A review of the problems of neutrino mass, mixing and oscillations is given. Possible phenomenological schemes of neutrino mixing are discussed. The most important consequences of neutrino mixing-neutrino oscillations are considered in some detail. The data of atmospheric, solar and LSND experiments are discussed. The results of phenomenological analysis of the data under the assumption of the mixing of three and four massive neutrinos are briefly presented.